Galectins: key players at the frontiers of innate and adaptive immunity - Martínez Allo, Verónica Candela (2018)
The proper function of the immune system entails multiple regulatory pathways aimed at modulating immunogenic and tolero-genic functions of immune cells. Galectins, a family of carbohydrate-binding proteins, control a variety of biological processes involved in activation, differentiation, trafficking and survival of immune cells. In this review we summarize pioneer work and emerging findings highlighting selected functions of galectins as regulatory checkpoints that control innate and adaptive immune cell programs.